2011
DOI: 10.1111/j.1469-8749.2011.03940.x
|View full text |Cite
|
Sign up to set email alerts
|

The forward parachute reaction and independent walking in infants with brain lesions

Abstract: FPRForward parachute reaction AIM The aim of this study was to assess the onset of forward parachute reaction (FPR) in infants with brain lesions and its correlation with age of walking.METHOD FPR was assessed at 6, 9, and 12 months in 140 infants with brain lesions (78 males, 62 females; mean gestational age 31wks; SD 3.6wks; mean birthweight 1450g, SD 252g). On cranial ultrasound 62 infants had mild and 78 had major abnormalities; 86 developed cerebral palsy. All were followed for 5 years, and the age at whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…reported in 8‐month‐old infants a moderate NPV of abnormal responses for CP. The other two studies indicated that the PPV of an absent parachute reaction for ‘no independent walking’ increased with age …”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…reported in 8‐month‐old infants a moderate NPV of abnormal responses for CP. The other two studies indicated that the PPV of an absent parachute reaction for ‘no independent walking’ increased with age …”
Section: Resultsmentioning
confidence: 97%
“…We restricted our review to neurological signs that were addressed in at least three different papers. This was true for six signs which were addressed in a total of 14 papers . First, we provide an overview of the predictive properties of the six signs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations